Emergency! - McDonough, Marjorie (Lippincott Williams & Wilkins home study continuing education booklet series, 1999)
A number of case studies are presented, with the symptoms, cause of problem, intervention techniques and follow up outlined for each. A test is also included at the end of the booklet.